The Effect of Green Marketing and Consumers’ Attitudes on Brand Image and Consumers’ Purchase Intention of Green Products in Denpasar - Luh Made Putri Juliantari; Putu Ngurah Suyatna Yasa; Ni Luh Putu Indiani (Jurnal Ekonomi dan Bisnis Jagaditha, 2019)
This study analyzed the effect of green marketing strategy and consumers’ attitudes on brand image and cunsumers’ intention of green products. This study uses a quantitative survey method. The object of this study is consumers’ purchace attitudes towards green products, with variables: attitude, green marketing, brand image, and purchase intention of green products. The data were collected through online surveys on participants who were lived Denpasar, were over 17 years old, and had their income, as well as having purchased the green products. The study found that the green marketing has a positive and significant effect on the brand image, which means that the better green marketing can improve the the brand image of green products. Apart from that, it is also discovered that the green marketing has a positive and significant effect on consumers’ purchase intention, which means that the better green marketing can increase the consumers’ purchase intention of green products. The attitudes of consumers have a positive but not significant effect on the brand image, which means that no matter how better the attitudes of the consumers, they could not improve the brand image of the green products significantly. The attitudes of consumers have has a positive but not significant effect on the consumers’ purchase intention, which means that no matter how better the consumers’ attitudes, they could not increase the purchase intentions of the consumers significantly. Brand image has a positive and significant effect on the consumers’ purchase intention, which means that the better the brand image, it will increase the the consumers’ intention to purchase the green products. Brand image is a partial mediation between green marketing and the consumers’purchase intentions because all direct and indirect relationships are significant, and the direct coefficient of green marketing's relationship with the purchase intention is greater than indirect compensation (indirect effect) for performance. Brand image is a full mediation between consumers’ attitudes and their purchase intentions.